(untitled) (Bangladesh Journal of Agricultural Research, 2018)
The released three varieties of bush bean (BARI Jhar Shim-1, 2 and 3) were grown in both Sclerotium rolfsii inoculated and un-inoculated plots to assess the yield loss in the field of Plant Pathology Division, Bangladesh Agricultural Research Institute (BARI), Gazipur during 2013. Sclerotium rolfsii infected the bush bean plant in every growth stage and reduced the germination capacity and lessened plant vigor. The yield loss ranged from 55.43 to 64.94%. A screening study was conducted to observe the resistant level of released varieties and local lines collected from On Farm Research Division (OFRD), BARI, Sylhet during 2013. B0124 and BARI Jhar Shim-3 showed susceptible and the others showed highly susceptible reaction. The antagonistic potential of the local isolates of Trichoderma harzianum against the phytopathogenic S. rolfsii was investigated in dual culture and bioassay on bean plants. Isolated T. harzianum showed antagonism effect against S. rolfsii and restricted around 80% mycelial growth in-vitro. A field experiment was carried out in Plant Pathology Division, BARI, Gazipur during 2014 to observe the efficacy of T. harzianum in controlling foot rot disease induced by S.rolfsii of bush bean in the field. Soil treated with T. harzianum mass plus seed treated with Provax 200 WP showed the lowest disease incidence (28.47%) and the highest germination (98.61%) and yield (873.33 kg/ha) in compared to other treatments with pathogen inoculated soil. Bangladesh J. Agril. Res. 43(2): 289-299, June 2018